Non-Formal Islamic Education in Building Social Harmony of Multicultural Farming Communities - Moh Ibnu Faruk Fauzi; Abd. Haris; Maulana Nur Kholis (WISE Pendidikan Indonesia, 2026)
This research explores how ethnic, cultural, and religious diversity can lead to social conflicts if not managed through inclusive, dialogical, and tolerance-based education. In Kaubun’s farming community, where time, human resources, and the quality of Islamic education are limited, non-formal Islamic education becomes crucial for teaching social and religious values. Using a qualitative case study approach, this study examines the social dynamics and religious practices within the community. Data was gathered through participatory observation, semi-structured interviews, and documentation with religious leaders, traditional leaders, village officials, and farming community members. Findings reveal that non-formal Islamic education plays a key role in promoting social harmony by transmitting religious knowledge and instilling values like tolerance, cooperation, and justice. Religious activities are adapted to fit the farming schedule, with sessions held after Maghrib prayers and integrated into local traditions like tahlilan and harvest celebrations. Factors supporting this include community awareness, the leadership of local figures, and government support. However, challenges such as limited time, a shortage of educators, difficult geography, and cultural and linguistic diversity impact participation and the effectiveness of the education provided.